PENGARUH PERMAINAN SMART BALL TERHADAP KEMAMPUAN MENGENAL WARNA PADA ANAK USIA DINI: THE EFFECT OF SMART BALL GAMES ON COLOR RECOGNITION ABILITY IN EARLY CHILDHOOD - Maulida, Susi; Fauziyah, Umi (Thufuli, 2020)
Child's cognitive development involves learning skills in children that occur through complex internal processes and mental activities. Children who develop both cognitive aspects will be able to learn to develop thought processes, respond to objects in their environment and reflect on their experiences. Sometimes children are not able to recognize colors because it is not usual to mention various colors and the limitations of the media to recognize colors when at school. Children only know certain colors that are often seen for example green because children see leaves, red and white when children see the flag and when children are faced with different objects the child will have difficulty guessing the color. Smart ball is a game tool that can develop children's cognitive play methods. Smart ball has advantages in developing all aspects of child development, especially in aspects of cognitive development, namely children are able to recognize colors. The approach in this research is a quantitative approach. Data collected in this study are descriptive. The process to be observed is student activities and teacher activities during the learning process. From the results of an analysis of the effect of smart ball on the ability to recognize colors, the results of research show that smartball games affect the ability to recognize children's colors.